2020
DOI: 10.1055/a-1255-2863
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cysteine Intake is Associated with Blood Glutathione Levels and Isometric Strength

Abstract: Glutathione is the most abundant cellular antioxidant and regulates redox homeostasis. Healthy individuals with certain antioxidant inadequacies/deficiencies exhibit impairments in physiological functions. The aim was to investigate whether low levels of dietary cysteine intake are associated with a) lower erythrocyte glutathione, b) increased plasma F 2 -isoprostanes, and c) impaired muscle function. Towards this aim, we recorded the dietary intake of the three amino acids that synthesize glutathione (i. e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
(97 reference statements)
0
12
0
Order By: Relevance
“…Methionine is an essential amino acid, whereas cysteine can be synthesized as long as sulfur is available. Sulfur is principally stored as glutatione (31), and sulfur deficiency may favor cysteine and protein synthesis at the expense of other molecules such as glutathione. Glutathione is a powerful antioxidant whose activity decreases with protein restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Methionine is an essential amino acid, whereas cysteine can be synthesized as long as sulfur is available. Sulfur is principally stored as glutatione (31), and sulfur deficiency may favor cysteine and protein synthesis at the expense of other molecules such as glutathione. Glutathione is a powerful antioxidant whose activity decreases with protein restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding antioxidant deficiencies, we have repeatedly shown that such deficiencies lead to increased resting oxidative stress levels and impaired exercise capacity (e.g., maximal oxygen uptake, muscle function, time trial performance). [65][66][67][68] Moreover, this impaired exercise capacity was reversed only when the antioxidant in deficiency was administered and not a random one. 13 Beyond exercise, a series of studies have shown that vitamin E deficiency (and predominantly the α-tocopherol isomer) adversely affects neural development and cognitive function, embryonic development, thiol homeostasis, while it also leads to genetic and transcriptional dysregulation resulting in metabolic dysfunction.…”
Section: Component Iv: Antioxidant Conditionmentioning
confidence: 99%
“…Regarding antioxidant deficiencies, we have repeatedly shown that such deficiencies lead to increased resting oxidative stress levels and impaired exercise capacity (e.g., maximal oxygen uptake, muscle function, time trial performance) 65–68 . Moreover, this impaired exercise capacity was reversed only when the antioxidant in deficiency was administered and not a random one 13 .…”
Section: Deconstructing and Decoding The Redox Signalmentioning
confidence: 99%
“…Specifically, the flawed assays of TBARS and TAC are inadequate today in redox biology ( 30 ). Considering spirulina contains approximately 0.45 g of cysteine/100 g and that adequate cysteine levels are essential for optimal glutathione concentration levels, redox status, and muscle function ( 31 ), equivocal results might also be attributed to the inter-individual baseline differences of glutathione before starting supplementation. For example, a recent study demonstrated that individuals with moderate-high baseline levels of glutathione did not benefit from N-acetylcysteine supplementation, yet those with low baseline levels improved V̇O 2max , time trial and Wingate tests by 13.6, 15.4, and 11.4%, respectively ( 32 ).…”
Section: Antioxidant Approachmentioning
confidence: 99%